Scholarly Communication Task Force Report and Recommendations - Andresen, Daniel; Carroll, Doris; Culbertson, Christopher; Gibson, Huston; Kastner, Justin; Kingery-Page, Katie; Lindshield, Brian; Markham, Mindy; Otto, Ryan; Porath, Suzanne; Suh, Jaebeom; Tatonetti, Lisa; et al. (Kansas State University, Manhattan, KS, 2020)
To address issues resulting from the serials crisis at Kansas State University, Provost Charles Taber, Faculty Senate President Tanya González, and Dean of Libraries Lori Goetsch created the Scholarly Communication Task Force during the 2019 fall semester. The purpose of this task force is to gather stakeholders in the K-State community to review the current landscape of scholarly communication practices on campus and offer recommendations to improve not only access to information at K-State but direct our institutional participation in the movement toward open scholarship. The task force reviewed scholarly communication initiatives at K-State and other higher education institutions and sought input from the campus community. Based on this information, the task force made several recommendations with accompanying budget implications. Recognizing that maintaining the status quo is not fiscally sustainable, we make the following recommendations: • We recommend that the University adopt an Open Access Policy to self-archive articles that it produces • We recommend the Library continue to monitor/manage subscription efficiencies • We recommend greater usage of interlibrary loan as an option for materials not subscribed to by K-State Libraries, while transitioning to transformational agreements and multipayer models • We recommend changes to how research is evaluated based on best practices • We recommend that faculty to write publication costs into their grant proposals • We recommend, continuing the Open Access fee fund, only if it is fully funded and higher priority recommendations are adequately supported Additional information about the task force’s findings and process for gathering information from the campus community are included later in this report.